Collaborative diabetes summit: a Malaysia-Pakistan cross-cultural clinical experience - Mohamed Shah, Fatimah Zaherah; Eddy Warman, Nur ‘Aini Eddy Warman; Awang, Mohd Hazriq Awang; Mohamad, Aimi Fadilah; Zainordin, Nur Aisyah; Abdul GhanI, Rohana (Faculty of Medicine, 2025)
Diabetes Mellitus (DM) is a condition of chronic hyperglycaemia resulting in many complications, leading to increases in morbidity and mortality. The prevalence of type- 2 DM in this region, particularly in Malaysia has been increasing at an exponential rate, and projected to rise even further in the coming years1,2. The Asian diabetes phenotype in part explains the increased incidence of DM among Asians3.